Effect of Plant Geometry on Different Rapeseed Varieties under Rainfed Upland Condition in Nepal - Adhikari, Susmita; Thapa, Binod; Poudel, Laxmi; Paudel, Prativa; Acharya, Ujjwal; Acharya, Bibek; Bohora, Sidda Lal (International Journal of Applied Sciences and Biotechnology, 2021)
The field experiment was carried out during winter of 2018/19 with two varieties (Unnati and Surkhet-Local) and three plant geometry (15cm × 10 cm, 30cm × 10 cm, 45cm × 10cm) in Randomized complete block design (RCBD) with four replications. Statistically there was no difference between two varieties while differences were found on different spacing and interaction between variety and spacing on final seed yield. High significant differences on seed yield was due to spacing and yield of rapeseed were higher at the 30 cm inter row spacing as compared to the 15 cm and 45 cm inter row spacing. Statistically significant effect was found on mean values of seed yield for interaction which showed that Unnati cultivar in 30 cm x 10 cm plant geometry had the highest seed yield (969.86 kg/ha) followed by Surkhet-local with spacing of 15 cm × 10 cm (843.75 kg/ha) and 30 cm × 10 cm (823.76 kg/ha). Yield of these varieties decreased as spacing is increased, thus sowing of Unnati should be done at cropping geometry of 30 cm × 10 cm and for Surkhet-local it should not be done beyond 30 cm inter row spacing to get the maximum potential yield. Int. J. Appl. Sci. Biotechnol. Vol 9(2): 113-121.